Analisa Faktor Eksternal pada Usaha Gadai Swasta dengan Layanan Pick Up - Lusy Aspriyani; Edi Hamdi (Universitas Batanghari, 2023)
Inside strategy competition Becomes role urgent for company in Upgrade superiority competitive. In the analysis strategy factor external needed for maintain and improve mark company in the industry kind. Aim from study in this is for Upgrade superiority competitive Pawnshop in compete on providers service service pawn existing conventional in Jakarta. For achieved his deep strategy aim that, researcher use method Porter,s Five Forces and PEST Analysis consist from factor politics, factor economic, social factors and factors technology. Result of study showing level competition industry Pawn in Jakarta counts enough high. Strategy used in resolve increasing competition strict between existing competitors that is with strengthen level differentiation product and maintain trust consumer with give easy and safe service. With using Porter’s Five Forces analysis strategy is expected Pawnshop capable compete and find out position competition as well as Upgrade superiority competitive for endure in market share.